EFFECT OF FUNGICIDES ON NITRATE UPTAKE AND ASSIMILATION IN ASPERGILLUSNIDULANS - U. Amin; N. Akhtar (Journal of Animal and Plant Sciences, 2017)
In present study, effect of three fungicides, Iprobenfos, Fosetylaluminium and Azoxystrobin, on substrate specificity of NrtA and NrtB nitrate transporter proteins of Aspergillus nidulans has been studied. Azoxystrobin inhibited the growth of A. nidulans strains more strongly than Iprobenfos and Fosetyl aluminium. At0.25R of Iprobenfos, approximately 82%, 85%, 76% growth inhibition was observed by wild type, nrtA1 and nrtB110respectively. Growth inhibition of wild type, nrtA1 and nrtB110 by recommended dose (R) of Fosetyl aluminium was 73%, 41% and 23%, respectively. 0.0075R of Azoxystrobin inhibited the growth of wild type, nrtA1 and nrtB110by 51%, 68% and 71%, respectively. Effect of Iprobenfos, Fosety laluminium and Azoxystrobinwas also studied on nitrate uptake of the A. nidulans strains. At 0.25R of Iprobenfos, 94%, 54% and 100% nitrate uptake inhibition was observed by wild type, nrtA1 and nrtB110 respectively. Recommended dose of Fosety laluminiumcompletely stopped the nitrate uptake by all strains. At 0.01R of Azoxystrobin, complete cessation in nitrate uptakeby nrtA1 and nrtB110was recorded however78% reduction in nitrate uptake was observedfor wild type strain.Increase in concentration of Iprobenfos(up to 0.25R), increasedthe nitrate reductase activity in wild type while decreased the enzymatic activity bynrtA1 and nrtB110strains. Recommended dose of Fosetylaluminiumand 0.0075R of Azoxystrobinenhanced nitrate reductase activity in wild type and nrtB110, however reduced theenzymatic activity in nrtA1. Present study concludes that excessive use of fungicides is not only a threat for environment but also reduces the nitrate uptake and assimilation efficiency of eukaryotes.
Keywords: Aspergillus nidulans; growth inhibition; nitrate uptake; pesticides